Mapping science: tools for bibliometric and altmetric studies - Osinska, Veslava; Klimas, Radoslaw (Information research, 2021)
Introduction. The study investigates whether online attention, carried out on social media or by video tutorials, affects the popularity of these tools in the research community. Method. We collected data from the Web of Science, Scopus, YouTube, Facebook, Twitter, and Instagram, using web-scraping tools. Bibliometrics, altmetrics and webometrics were applied to process the data and to analyse Gephi, Sci2 Tool, VOSviewer, Pajek, CiteSpace and HistCite. Analysis. Statistical and network analyses, and YouTube analytics, were used. The tools’ interfaces were assessed in the preliminary stage of the comparison. The results were plotted on charts and graphs, and compared. Results. Social media and video tutorials had minimal influence on the popularity of different tools, as reflected by the number of papers within the Web of Science and Scopus where they featured. However, the small but constant growth of publications mentioning Gephi could be a result of Twitter promotion and a high number of video tutorials. The authors proposed four directions for further comparisons of science mapping software. Conclusions. This work shows that biblio- and scientometricians are not influenced by social media visibility or accessibility of video tutorials. Future research on this topic could focus on evaluating the tools, their features and usability, or the availability of workshops.